1987
DOI: 10.1111/j.1348-0421.1987.tb03114.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Reactive Antibodies to Mycoplasmas Found in Human Sera by the Enzyme‐Linked Immunosorbent Assay (ELISA)

Abstract: Antibodies against Mycoplasma pneumoniae in patients' sera with M. pneumoniae infection were measured by the complement fixation (CF) test and enzyme‐linked immunosorbent assay (ELISA). Many patients' sera cross‐reacted with heterologous mycoplasmal ELISA antigens such as M. hominis, M. hyorhinis, M. orale, M. pulmonis and M. salivarium. The sera with high CF (CF≥40) titers gave significantly higher ELISA values to M. hyorhinis (P<0.001) and M. pulmonis (P<0.001), which are not parasitic for humans, than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…With the sera from patients infected only by C. trachomatis, reactivity occurred in 6% of cases, whereas with the sera from patients infected by other mycoplasmas (M. hominis or M. pneumoniae), reactivity occurred in 24% of cases. These findings were in agreement with the previous results of Brown et al (1), Lind and Kristensen (13), and Sasaki et al (16). In the literature, neither mycoplasma is known to cross-react with ureaplasma, and this is not surprising since they are quite distinct organisms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With the sera from patients infected only by C. trachomatis, reactivity occurred in 6% of cases, whereas with the sera from patients infected by other mycoplasmas (M. hominis or M. pneumoniae), reactivity occurred in 24% of cases. These findings were in agreement with the previous results of Brown et al (1), Lind and Kristensen (13), and Sasaki et al (16). In the literature, neither mycoplasma is known to cross-react with ureaplasma, and this is not surprising since they are quite distinct organisms.…”
Section: Discussionsupporting
confidence: 93%
“…Of the 17 patients who had C. trachomatis infection, 16 (94%) were seronegative (mean A4, value, 0.062).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we also showed that the nonspecific adsorption of human normal IgG on the surface of plate wells and on medium components which might contaminate in M. pneumoniae antigen could be disregarded (21). These results suggested the existence of the cross-reactive antibodies to mycoplasmas that lowered the specificity of the ELISA in serodiagnosis of M. pneumoniae infection.…”
mentioning
confidence: 76%
“…We previously showed by the ELISA that varying levels of cross-reactivity to some mycoplasma species were seen in human normal immunoglobulin G (human normal IgG) prepared from pooled plasma of at least 500 normal human donors and in some human sera not associated with M. pneumoniae infections (21). Furthermore, we also showed that the nonspecific adsorption of human normal IgG on the surface of plate wells and on medium components which might contaminate in M. pneumoniae antigen could be disregarded (21).…”
mentioning
confidence: 99%
“…However, the diagnosis can be hampered by cross reactions between M. pneumoniae and other commensal mycoplasms among the oropharyngeal florae. There are different opinions on this issue in the literature: a cause of error for some authors [12], a negligible parameter for others [13]. At present, the IgA ELISA tests have a sensitivity of 86 to 100% and a specificity of 100% for the serologic diagnosis of acute M. pneumoniae infection [14].…”
Section: Indirect Diagnosismentioning
confidence: 99%